2002
DOI: 10.1051/0004-6361:20020554
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous age dating of 55 Galactic globular clusters

Abstract: Abstract. We present homogeneous age determinations for a large sample of 55 Galactic globular clusters, which constitute about 30% of the total Galactic population. A study of their age distribution reveals that all clusters from the most metal poor ones up to intermediate metallicities are coeval, whereas at higher [Fe/H] an age spread exists, together with an age-metallicity relationship. At the same time, all clusters within a certain galactocentric distance appear coeval, whereas an age spread is present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
308
3
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(353 citation statements)
references
References 40 publications
(63 reference statements)
41
308
3
1
Order By: Relevance
“…Even if our purpose is only to check the general agreement between the present set of models and data, we note that our estimates for age, distance modulus and reddening are consistent, within the uncertainties, with the recent ones available in the literature (see e.g. di Cecco et al 2010;Kraft & Ivans 2003;Salaris & Weiss 2002;VandenBerg et al 2002, for M92;Kraft & Ivans 2003;Rey et al 2001;Yi et al 2001, for M3;Bergbusch & Stetson 2009;Percival et al 2002;Grundahl et al 2002, andreferences therein, Zoccali et al 2001, for 47 Tuc). We are aware that very high quality photometric data for 47 Tuc show the possible presence of multipopulation from the analysis of the subgiant branch (see e.g.…”
Section: Comparison With Observational Datasupporting
confidence: 83%
“…Even if our purpose is only to check the general agreement between the present set of models and data, we note that our estimates for age, distance modulus and reddening are consistent, within the uncertainties, with the recent ones available in the literature (see e.g. di Cecco et al 2010;Kraft & Ivans 2003;Salaris & Weiss 2002;VandenBerg et al 2002, for M92;Kraft & Ivans 2003;Rey et al 2001;Yi et al 2001, for M3;Bergbusch & Stetson 2009;Percival et al 2002;Grundahl et al 2002, andreferences therein, Zoccali et al 2001, for 47 Tuc). We are aware that very high quality photometric data for 47 Tuc show the possible presence of multipopulation from the analysis of the subgiant branch (see e.g.…”
Section: Comparison With Observational Datasupporting
confidence: 83%
“…The metal-poor clusters in Sgr appear to be approximately coeval with the oldest Galactic globular clusters (e.g., Layden & Sarajedini 2000), which according to recent studies (e.g., Salaris & Weiss 2002) have ages of 12 to 13 Gyr. The identification of Whiting 1 with Sgr suggests that this galaxy was able to form star clusters for ≈6 Gyr.…”
Section: Whiting 1 and The Star Cluster Family Of The Sgr Dsphmentioning
confidence: 78%
“…According to Sandquist (2004) and references therein, M 67 is 4 Gyr old and has approximately solar composition. M71 is much older, ∼10 Gyr, and more metal poor, [Fe/H] ∼ -0.7 (e.g., Salaris & Weiss 2002). In the upper diagram of Fig.…”
Section: Estimate Of Metallicity From the Infrared Caii Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Past observations have shown that galactic metal-poor GCs tend to be older than metal-rich GCs and the age spread in metal-poor GCs is ∼ 1 Gyr compared to the ∼ 6 Gyr dispersion in metal-rich GCs (Rosenberg et al 1999;Salaris & Weiss 2002;Marín-Franch et al 2009). There is some evidence of self enrichment in GCs; however, the age gap between metal-poor and metal-rich GCs is greater than the range present within each population suggesting that these are two distinct populations (Marín-Franch et al 2009).…”
mentioning
confidence: 96%